Reduced automatic approach tendencies towards task-relevant and task-irrelevant food pictures in Anorexia Nervosa. (December 2019) - Neimeijer, Renate A.M.; Roefs, Anne; Glashouwer, Klaske A.; Jonker, Nienke C.; de Jong, Peter J.
Abstract: Background and objectives: Anorexia Nervosa (AN) patients are characterized by an excessive restriction of their food-intake. Prior research using an Affective Simon Task (AST) with food as a task-irrelevant feature, provided evidence for the view that AN patients' ability to refrain from food is facilitated by reduced automatic approach tendencies towards food. However, because food was task-irrelevant (i.e., participants had to base their reaction on the perspective of the picture and not on its content), the findings may in fact reflect a relatively strong ability to ignore the content of the food stimuli rather than weakened approach towards food per se. Therefore, this study also included a Stimulus Response Compatibility (SRC) task with food as task-relevant feature that could not be ignored, because the required response depended on the [food vs non-food] content of the pictures. Methods: AN spectrum patients ( n  = 63), and a comparison group of adolescents without eating pathology ( n  = 57) completed both a SRC task with food as task-relevant feature, and an Affective Simon Task AST with food as task-irrelevant feature. Results: AN patients showed reduced approach tendencies for high caloric food. Only the SRC uniquely predicted the presence of AN. Limitations: Comparison between tasks was hampered because the SRC only included high caloric food stimuli, whereas the AST included high and low caloric food stimuli. Conclusion: Patients with AN are characterized by weakened automatic approach of high caloric food. This might 'help' restrict their food-intake even in a condition of starvation. Highlights: Automatic approach tendencies (AAT) were tested in girls with Anorexia (AN). In one task food was task-irrelevant, and could thus be ignored. In a second task food was task-relevant and could thus NOT be ignored. Girls with AN showed reduced AAT for food also when food could not be ignored. These reduced AAT towards food may contribute to the persistence of AN.